Communicative Situation and Linguistic Composition of a Target text in Specialised Translation: Contextual and Conceptual Aspect - R. M. Shamilov; V. V. Sdobnikov (Научный диалог)
The article highlights the dependence of the degree to which the content of the source text is reproduced in translation on the peculiarities of the communicative situation and the translation strategy. The problem is topical due to the need to specify the strategies of specialized translation in the framework of the communicative-functional approach to translation. Three types of strategies as well as communicative situations in which translation is used are defined. The text of a register receipt and its translations is used for analysis. Special attention is paid to substantiation of the necessity to take into account the needs of the target text recipient and the translation goal in choosing a translation strategy and the means of its implementation. The authors argue that the content of a specialized text is reproduced in translation to the degree which is predetermined by the characteristics of the substantive activity of the target text end-user. It is also argued that the provisions of the so called text-oriented approach to translation have no validity for choosing a strategy of translating a specialized text. The research is innovative for the fact that it proves that there is no need to reproduce the content of a specialized text in full in some communicative situations. The notion of ergonomics of translation defined as convenience to use the target text by its recipient is novel.